A Conceptual Discussion About the Basic Reproduction Number of Severe Acute Respiratory Syndrome Coronavirus 2 in Healthcare Settings. (30th May 2020) - Temime, Laura; Gustin, Marie-Paule; Duval, Audrey; Buetti, Niccolò; Crépey, Pascal; Guillemot, Didier; Thiébaut, Rodolphe; Vanhems, Philippe; Zahar, Jean-Ralph; Smith, David R M; Opatowski, Lulla
Abstract: To date, no specific estimate of R0 for SARS-CoV-2 is available for healthcare settings. Using interindividual contact data, we highlight that R0 estimates from the community cannot translate directly to healthcare settings, with pre-pandemic R0 values ranging 1.3–7.7 in 3 illustrative healthcare institutions. This has implications for nosocomial COVID-19 control.